2018
DOI: 10.2147/ott.s166961
|View full text |Cite
|
Sign up to set email alerts
|

<em>HOXA11-AS</em>: a novel regulator in human cancer proliferation and metastasis

Abstract: Multiple studies have demonstrated that lncRNAs extensively participate in human cancer proliferation and metastasis. Epigenetic modification, transcriptional and posttranscriptional regulatory mechanisms are involved in lncRNA-led tumorigenesis and transfer. Recently, a novel identified homeobox (HOX) A11 antisense lncRNA, HOXA11-AS, 1,628 bp in length, has been excessively highlighted to be an essential initiator and facilitator in the process of malignant tumor proliferation and metastasis. As found in many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 68 publications
(64 reference statements)
0
40
0
Order By: Relevance
“…20 However, two studies have ascribed a role to HOXA11-AS as a tumour suppressor gene in colorectal and epithelial ovarian cancer. 20 In addition, HOXA11-AS has been suggested to delay fracture healing by inhibiting proliferation and promoting apoptosis. 12 Furthermore, in a recent research, HOXA11-AS has been reported to promote proliferation, migration and inflammation-related gene expression, thereby spurring inflammation in diabetic arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, two studies have ascribed a role to HOXA11-AS as a tumour suppressor gene in colorectal and epithelial ovarian cancer. 20 In addition, HOXA11-AS has been suggested to delay fracture healing by inhibiting proliferation and promoting apoptosis. 12 Furthermore, in a recent research, HOXA11-AS has been reported to promote proliferation, migration and inflammation-related gene expression, thereby spurring inflammation in diabetic arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…First, metastasis is an essential hall marker of cancer and always leads to poor survival. [41][42][43] Numerous studies suggested that Tiam1 contributed to invasion and metastasis in various cancers, including osteosarcoma, 44 retinoblastoma, 45 gastric cancer, 46 CRC, [47][48][49][50][51] hepatocellular carcinoma, 25,52 breast cancer, 53 cholangiocarcinoma, 54 cervical cancer, 20 ovarian cancer, 55 nasopharyngeal cancer, 8,16 laryngeal cancer, 56 thyroid carcinoma, 57 nom-small cell lung cancer, 48 pancreatic cancer 6,58,59 and oral squamous cell carcinoma 27 Malliri et al reported that Tiam1 could facilitate E-cadherin-based adhesions between cancer cells in mouse intestinal tumors and human colon tumors, resulting in invasion and metastasis 60 Epithelial-mesenchymal transition (EMT) is a key process of enhancing cancer cell migration, invasion and metastasis. [28][29][30][31] Liu et al reported that Tiam1 overexpression could promote invasiveness and metastasis of thyroid carcinoma in vitro and in vivo by activating Wnt/EMT pathway 57 Similarly, Ding 6 and Yang et al 20 that Tiam1 overexpression could also boost invasion and metastasis of pancreatic cancer and cervical cancer by inducing EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) play important roles in tumor growth and metastasis and are linked to the activation of oncogenic signaling pathways or inactivation of tumor-suppressive signaling in the nucleus [4,5]. Although most functions of lncRNAs and miRNAs have not been clarified, recent evidence indicates that they are involved in the regulation of CRC proliferation and metastasis [6].…”
Section: Ivyspringmentioning
confidence: 99%